Six new triterpenoids from the root of Potentilla reptans and their cardioprotective effects in silico. Issue 10 (23rd May 2022) - Enayati, Ayesheh; Salehi, Aref; Alilou, Mostafa; Stuppner, Hermann; Mirzaei, Hasan; Omraninava, Aghigh; Khori, Vahid; Yassa, Narguess
Abstract: Tormentic acid ester glucosides derivatives (1, 2 and 4 ), 3-oxoursane ester glycoside (3 ) and 11-methoxy-ursane ester glycosides (5, 6 ) as six new triterpenoids, along with catechin were isolated from the ethyl acetate fraction of Potentilla reptans root (Et) methanolic extract. The structures of the compounds were elucidated by 1D, 2D NMR, IR and MS spectroscopy. Additionally, isolated triterpenoid compounds (1–6 ) and catechin were evaluated for their cardioprotective effects via glycogen synthase kinase 3β (GSK-3β) and glucocorticoid regulated kinase-1 (SGK1) protein kinase inhibition by Molecular Docking. Compound 1 and catechin (compound 7 ) exhibited significant inhibitory effects against GSK-3β and SGK1 protein kinases with a binding energy value −9.1 and −8.8 kcal/mol, respectively. Hence, Et can be a suitable natural candidate to protect cardiomyocytes injury. Graphical abstract: UF0001